Increasing the legal retirement age: the impact on wages, worker flows and firm performance - Pedro Silva Martins; Álvaro A. Novo; Pedro Portugal (Institute for the Study of Labor (IZA), 2009)
Many pay-as-you-go pension systems have increased or plan to increase their legal retirement age (LRA) to address the financial consequences of ageing. Although the success of these policies is ultimately determined at the labour market, little is known about the effects of higher LRAs at the firm level. Here, we identify this effect by considering a legislative reform introduced in Portugal in 1994: women's LRA was gradually increased from 62 to 65 years while men's LRA stayed unchanged at 65. Using detailed matched employer-employee panel data and difference-in-differences matching methods, we analyse the effects of the reform in terms of a number of worker- and firm-level outcomes. After providing evidence of compliance with the law, we find that the wages and hours worked of older women (those required to work longer) were virtually unchanged. However, firms employing older female workers significantly reduced their hirings, especially of younger female workers. Those firms also lowered their output although not their output per worker.
urn:nbn:de:101:1-20090612114
Keywords: J14; J26; J63; 330; Social security reform; older workers; matching estimators; Altersgrenze; Gesetzliche Rentenversicherung; Rentenreform; Frauenerwerbstätigkeit; Ältere Arbeitskräfte; Arbeitsnachfrage; Frauenarbeitslohn; Arbeitsmobilität; Unternehmensentwicklung; Portugal